Menelaah Koeksistensi Damai antara Komunitas Sunni dan Syiah di dusun Sendangasari Kabupaten Jepara - Andi Ahmad Rukka Haryadi (LITERATUS, 2020)
This research is aim to explain the causes of peace coexistence between Sunni and Shia community in dusun Sendangsari, kabupaten Jepara. Type of research method that use are qualitative with snowball of chain sampling as the main technique to collecting data for analysis. There are three hyphothesis which researcher use to explain the causes of peace in this research, first is to observe how the structure of civic life between this two communities, second self policing as the mechanism to contain violence, and third how elite integration would contribute to explain the peace coexistence. The results show that the structure of civic life which cut the religion ethnic lines between two communities stand as important causes. There were 5 form of civic engagement as part of the finding in this research, and extent to mechanism of self policing that containing violence. Consensus on cultural and structural context that marked the elite integration, legitimize the peace behaviours between this two communites, and at the same time delegitimize the intolerance perception or behaviour that would affect the peace relationship between Sunni and Shia community. Also, this peace coexistence cannot be separated from the cognitive fact which stand as collective consciousness (norm) of the two communities, which are : Religion faith is part of individual rights, but public affairs are responsibilities of every individual who live in dusun Sendangsari.